EVALUATION AND JOB MOTIVATION ANALYSIS IN IMPROVING EMPLOYEE PERFORMANCE - Irwan Sugiarto; Yuliana Yuliana; Lilis Suryani; Suflani Suflani (Yayasan Education and Social Center, 2022)
Human Resource Management which cannot manage globalization, requires work is a burden. They carry out work as a necessity and demand, and then human resources can be said to have a low work ethic. This study aims to determine the evaluation and analysis of work motivation in improving employee performance. The type of search used is descriptive qualitative, which is the symptoms and facts of the object when the research occurs. Data collection techniques used in this study were interviews and extensive documentation. The results showed that work motivation is significant for employees to support their performance. And performance, we can say helpful in creating job satisfaction for employees and can improve the company's image